2000
DOI: 10.1023/a:1008111328771
|View full text |Cite
|
Sign up to set email alerts
|

Untitled

Abstract: In order to establish an easy and quick construction method for obtaining a stable and highly productive gene-amplified recombinant Chinese Hamster Ovary (CHO) cell line, variouskinds of stepwise methotrexate (MTX) selection were carriedout. The specific growth and production rates of the cell were compared with each other, and the distribution of the amplified gene location was determined using fluorescence in situ hybridization (FISH). The specific growth andproduction rates of the cell pool reached the high… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2008
2008
2019
2019

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 43 publications
(13 citation statements)
references
References 36 publications
1
12
0
Order By: Relevance
“…All three cell lines showed different levels of productivity, gene copy number and mRNA content. Previous studies have also reported that despite being derived from a single clone, cell lines can become quite heterogeneous following MTX amplification [11,41,51]. All non-UCOE cell lines had reduced productivity over longterm culture in the absence of MTX, with a *90 % decrease in productivity, which contrasted with a *50 % loss of gene copy that was observed in the absence of MTX.…”
Section: Discussionmentioning
confidence: 85%
“…All three cell lines showed different levels of productivity, gene copy number and mRNA content. Previous studies have also reported that despite being derived from a single clone, cell lines can become quite heterogeneous following MTX amplification [11,41,51]. All non-UCOE cell lines had reduced productivity over longterm culture in the absence of MTX, with a *90 % decrease in productivity, which contrasted with a *50 % loss of gene copy that was observed in the absence of MTX.…”
Section: Discussionmentioning
confidence: 85%
“…To investigate the efficiency of CRISPR-Cas9 gene targeting in CHO cells, the frequency of gene integration into chromosome O was analyzed. In a previous study, chromosome O was identified as a suitable target site for stable and highly efficient exogenous gene expression [ 3 ]. In Figure 1, red signals indicate the BAC clone Cg0031N14 hybridized to chromosome O.…”
Section: Resultsmentioning
confidence: 99%
“…Early studies [ 14 ] have shown that telomere-type clones, in which the exogenous gene is located near the telomeric region, were found to have a specific hGM-CSF production rate, approximately 6 times higher than the rate of other type of clones. Our study also provided evidence that the telomeric region at chromosome 1 appears to be a desired site for exogenous gene integration.…”
Section: Discussionmentioning
confidence: 99%
“…Analysis of a broad range of recombinant cell lines and their integration loci found that the majority of highly producing cell lines have an insertion locus on large chromosomes [ 4 , 6 ]. The fragile site and the telomeric region have been proposed to be the preferred integration site of the stable transfectant [ 13 , 14 ]. However, others have suggested that gene integration at known fragile sites can lead to genomic instability, thus affecting the expression of targeted genes [ 15 ].…”
Section: Introductionmentioning
confidence: 99%